Cause of death in spontaneous intracerebral hemorrhage survivors: Multistate longitudinal study. (17th November 2020) - Kuohn, Lindsey R.; Leasure, Audrey C.; Acosta, Julian N.; Vanent, Kevin; Murthy, Santosh B.; Kamel, Hooman; Matouk, Charles C.; Sansing, Lauren H.; Falcone, Guido J.; Sheth, Kevin N.
Abstract : Objective: To determine the leading causes of death in intracerebral hemorrhage (ICH) survivors, we used administrative data from 3 large US states to identify adult survivors of a first-time spontaneous ICH and track all hospital readmissions resulting in death. Methods: We performed a longitudinal analysis of prospectively collected claims data from hospitalizations in California (2005–2011), New York (2005–2014), and Florida (2005–2014). Adult residents admitted with a nontraumatic ICH who survived to discharge were included. Patients were followed for a primary outcome of any readmission resulting in death. The cause of death was defined as the primary diagnosis assigned at discharge. Multivariable Cox proportional hazards and multinomial logistic regression were used to determine factors associated with the risk for and cause of death. Results: Of 72, 432 ICH survivors (mean age 68 years [SD 16], 48% female), 12, 753 (18%) died during a median follow-up period of 4.0 years (interquartile range 2.3–6.3). The leading causes of death were infection (34%), recurrent intracranial hemorrhage (14%), cardiac disease (8%), respiratory failure (8%), and ischemic stroke (5%). Death in patients with atrial fibrillation (AF) was more likely to be caused by ischemic stroke (odds ratio [OR] 2.4, 95% confidence interval [CI] 1.9–2.9, p < 0.001) and less likely to be caused by recurrent intracranial hemorrhage (OR 0.7, 95% CI 0.6–0.8, p < 0.001) compared to patients without AF. Conclusions: Infection is the leading cause of death in all ICH survivors. Survivors with AF were at increased risk for death from ischemic stroke. These findings will help prioritize interventions aimed to improve long-term survival and recovery in ICH survivors.